Lipid Phase Behaviour of the Curvature Region of Thylakoid Membranes of Spinacia oleracea - Bode, Kinga; Trotta, Andrea; Dlouhy, Ondrej; Javornik, Uros; Paakkarinen, Virpi; Fujii, Hiroaki; Domonkos, Ildiko; Zsiros, Otto; Plavec, Janez; Špunda, Vladimir; Aro, Eva-Mari; Garab, Győző (Wiley, 2025)
Thylakoid membranes (TMs) of oxygenic photosynthetic organisms are flat membrane vesicles, which form highly organised, interconnected membrane networks. In vascular plants, they are differentiated into stacked and unstacked regions, the grana and stroma lamellae, respectively; they are densely packed with protein complexes performing the light reactions of photosynthesis and generating a proton motive force (pmf). The maintenance of pmf and its utilisation for ATP synthesis requires sealing the TMs at their highly curved regions (CRs). These regions are devoid of chlorophyll-containing proteins but contain the curvature-inducing CURVATURE THYLAKOID1 (CURT1) proteins and are enriched in lipids. Because of the highly curved nature of this region, at the margins of grana and stroma TMs, the molecular organisation of lipid molecules is likely to possess distinct features compared to those in the major TM domains. To clarify this question, we isolated CR fractions from Spinacia oleracea and, using BN-PAGE and western blot analysis, verified that they are enriched in CURT1 proteins and in lipids. The lipid phase behaviour of these fractions was fingerprinted with P-31-NMR spectroscopy, which revealed that the bulk lipid molecules assume a non-bilayer, isotropic lipid phase. This finding underpins the importance of the main, non-bilayer lipid species, monogalactosyldiacylglycerol, of TMs in their self-assembly and functional activity.